Refleksi Teologis Melalui Metode Sharing Christian Praktis (SCP) dalam Pendidikan Kristen: Integrasi Iman dan Pengalaman Hidup - Litri Yerisa Eribka; Sandro Apriedo; Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Christian education plays a strategic role in shaping the faith, character, and spiritual life of learners however, learning processes often remain theoretical, limiting the internalization of faith values. This study aims to examine the concept of theological reflection using the Sharing Christian Praxis (SCP) method in Christian education, explore its application, and analyze its relevance to contemporary life. This research employs a qualitative approach with a literature study method, drawing on relevant books, scientific journals, and academic sources. The findings indicate that theological reflection is a fundamental process in Christian education that enables learners to interpret life experiences in the light of God’s Word, resulting in authentic faith transformation. The SCP method, developed by Thomas H. Groome, provides an operational framework for implementing this theological reflection through systematic stages: sharing life experiences, critical reflection, engagement with Scripture, dialogue, and commitment to action. The relationship between theological reflection and SCP is integral and synergistic; theological reflection provides direction and depth, while SCP operationalizes this process dialogically and contextually, the application of SCP in Christian education has proven effective in increasing learner engagement and connecting faith with daily life. It is recommended that Christian educators implement SCP as a primary learning method, and that educational institutions integrate it into their curriculum development strategies.